Analisis Keputusan Penumpang Dalam Menggunakan Kapal KM. Egon (Studi pada PT. Pelni Cabang Surabaya) - Gembong Satri Negara; Iwan Weda (Master Manajemen, 2023)
Passenger ship is a moving interior space media, where the interior space formed in it should be able to support the needs of its passengers during their trip. Passenger decisions in choosing a ship are influenced by various factors, including service quality, company image, and safety assurance. This study aims to determine the effect of service quality, company image, and safety assurance on passenger decisions in using the KM. Egon. This study uses data collection methods carried out by questionnaires as many as 93 respondents of KM passengers. Egon and the data was analyzed by multiple linear regression. The results showed that service quality, company image, and safety assurance had an effect on passenger decisions in using the KM. Egon.